Familial Concentration and Distribution of Adolescent Victimization: An Analysis of Factors that Promote and Protect Siblings from Victimization. Issue 6 (18th August 2019) - Rima, Dzhansarayeva; Yerbol, Alimkulov; Adlet, Yergali; Sholpan, Malikova; Beaver, Kevin M.
ABSTRACT: Findings from a significant body of research have consistently revealed that the majority of all criminal behavior is concentrated in a relatively small proportion of all families. Given the strong connection between criminal offenders and victims of violence, it is interesting that no research to date has examined whether victimization also concentrates within families. The current study sought to address this gap in the literature by examining adolescent victimization in a sample of kinship pairs drawn from the National Longitudinal Study of Adolescent to Adult Health (Add Health). Analyses of these data revealed that acts of serious victimization that occur during adolescence tend to concentrate in a small proportion of all families. Specifically, almost all serious victimization incidents were found to be concentrated in approximately 25 percent of all families. Additional analyses examined the familial factors that might explain sibling differences in victimization and the results did not uncover any family-level factors that explained why one sibling might be more likely to be victimized than the other. We conclude by noting the limitations of the study and offering directions for future research.